RARE-14. Newborn with hypothalamic hamartoma and Pallister-Hall syndrome. (3rd June 2022) - Flaßkühler, Anna Meera; Friedrich, Carsten; Beckhaus, Julia; Boekhoff, Svenja; Fiedler, Kai; Becking, Mechthild Schulze; Hitz, Marc-Philipp; Gieldon, Laura; Spranger, Stephanie; Bison, Brigitte; Hoppe, Florian; Müller, Hermann L
Abstract: A female full-term newborn of 41 + 2 weeks gestational age with a respiratory adaptation disorder and hypercapnia was transferred from an external maternity clinic to our pediatric intensive care unit. The child is the second child of healthy, non-consanguineous parents. Multiple dysmorphias were noticed at arrival. We identified a choanal atresia/stenosis on both sides in the respiratory tract, a high palate, a submucous cleft palate, a bifid uvula, a laryngeal cleft and a bronchus suis. The child required intubation and ventilation. In addition, we recognized brachydactyly of the hands and feet. The phalanges were not visibly separable. There was nail hypoplasia and rocker bottom feet on both sides. Furthermore, we saw an anal atresia. In routine laboratory work-up, a hypoglycemia and not measurable low TSH serum concentration was noticed. Extended endocrinological laboratory diagnostics revealed a complete pituitary insufficiency. On cranial MRI, a large, iso- to slightly hyperintense space-occupying mass (3.8x3.7x2.5 cm 3 ), originating from the hypothalamus was observed. The brainstem was displaced posteriorly by the mass. The imaging is consistent with a hypothalamic hamartoma. With regard to the present findings, we assumed an underlying genetic cause of the congenital malformations. As a clinical diagnosis, a Pallister-Hall syndrome was suspected. As described in our case, we saw the characteristic features: dysmorphia of the hands and feet, upper respiratory tract, anal atresia, and hypothalamic hamartomas. The Pallister-Hall syndrome is caused by mutations in the GLI3 gene on the 7p13 chromosome. It is inherited in an autosomal dominant manner and its prevalence is unknown. In our patient, a heterozygous, probably pathogenic variant in the GLI3-Gene was proven by Next Generation Sequencing (NGS).